Deutsche Jesuiten in Japan - Fuess, Harald (Japanstudien, 2006)
Many scholars have analyzed the early modern history of Iberian Jesuit missionaries in Japan, but there has been virtually no study on the subject of the Jesuit mission in the twentieth century. Based on archival documents and interviews, this essay argues that German Jesuits played a key historical role in the establishment and initial development of the modern Jesuit presence in Japan. Because most Jesuits who arrived in the prewar period were of German background, personal connections and strong institutional and financial ties existed between the Jesuit communities in both countries until well into the 1960s. The most influential activities of these German missionaries, especially in the early decades, were teaching German language and culture to a Japanese audience and disseminating knowledge about Japan to the Western world. This paper shows how the larger political and cultural relations between Germany and Japan during both peace and wartime limited, and at the same time enabled, the work of these German Jesuit missionaries.
Gesehen am 07.07.2022